Старый завет: стихотворения / П. П. Любомиров - Любомиров Петр Петрович (Удмуртия, 1991)
Экземпляры: КР (20020330) / Инвентарный номер: у40416 / Цена: 0.25 / Сис.шифр: Р2 / Авт.знак: Л 93 / ГРНТИ: 17 / ББК: 84(2)